THE IMPORTANCE OF ACTIVATING STUDENTS' INDEPENDENT CREATIVE ACTIVITIES (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
In the article, in order to activate the independent creative activities of students in higher education, it is necessary to effectively organize and conduct independent work, the correctness, accuracy, authenticity, veracity of the things and events that the student reflects, perceives, perceives, imagines, remembers in the activity of independent thinking, or their correspondence to reality. appropriateness and lack of understanding, judgments, concepts, conclusions, hypotheses (assumptions) formed in the process of knowledge of existence, determination of truth or falsity in making decisions, indirect or direct reflection of reality by summarizing, internal, complex connections between things and events , understands and comprehends relations, properties, features and mechanisms, the student can notice and predict the emergence, passage, development of natural and social phenomena and events based on specific laws, rules and regulations, the ability to foresee and predict the student's cognitive and practical activities , it is recognized that the importance of independent thinking is of particular importance in organizing effectively, the importance and necessity of developing students' independent thinking abilities.